1995
DOI: 10.1143/jjap.34.2650
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Diffraction Grating Assisted by Surface Acoustic Wave

Abstract: It was found for the first time that a diffraction grating was formed by perturbation in film thickness and refractive index with period of half the wavelength of surface acoustic waves, when thin film was deposited on substrate in which standing surface wave was excited. No such phenomenon has been reported so far, and its application to optical elements is hoped to be a new applications of surface acoustic waves.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Nakagawa et al found that when a Ta 2 O 5 thin film is fabricated by sputtering while applying SAW excitation to the substrate to form the film, the refractive index and the optoelastic constant of the thin film are increased [2]. In the course of this study, they also found that undulations were produced on the surface of the thin film and that a phase grating was formed in which the refractive index varied periodically [3]. This phenomenon is new and very interesting.…”
Section: Introductionmentioning
confidence: 51%
See 2 more Smart Citations
“…Nakagawa et al found that when a Ta 2 O 5 thin film is fabricated by sputtering while applying SAW excitation to the substrate to form the film, the refractive index and the optoelastic constant of the thin film are increased [2]. In the course of this study, they also found that undulations were produced on the surface of the thin film and that a phase grating was formed in which the refractive index varied periodically [3]. This phenomenon is new and very interesting.…”
Section: Introductionmentioning
confidence: 51%
“…Figure 7 shows that if opposite phase is assumed, a case can arise in which the change of the refraction index is zero. The conclusion that the change of the refraction index can be zero, however, does not match past experimental results [3], and physically it is a contradiction. Consequently, the relationship between the peak positions of the refraction index and the phase grating ripple is in-phase, i.e., the refraction index is larger at the peak of the phase grating ripple.…”
Section: Determination Of Film Thickness and Refraction Index Variationsmentioning
confidence: 76%
See 1 more Smart Citation
“…As for the applications using a standing wave of a surface acoustic wave excited on a substrate, Nakagawa and coworkers fabricated a thin-film phase grating and attained an energyefficient optical modulator. [14][15][16][17][18][19] The two-dimensional pattern was hardened with UV irradiation for 5 min using a black light (Toshiba EFD15BLB, 15 W). The UV hardening process is based on photopolymerization, which means phase change from monomer to polymer triggered by UV light.…”
mentioning
confidence: 99%